2016
DOI: 10.1016/j.athoracsur.2015.10.083
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Ischemic Mitral Regurgitation After Posterolateral Myocardial Infarction in Sheep Alters Left Ventricular Shear but Not Normal Strain in the Infarct and Infarct Borderzone

Abstract: Background Chronic ischemic mitral regurgitation (CIMR: MR) is associated with poor outcome. Left ventricular (LV) strain after postero-lateral myocardial infarction (MI) may drive LV remodeling. Although moderate CIMR has been previously shown to effect LV remodeling, the effect of CIMR on LV strain after postero-lateral MI remains unknown. We tested the hypothesis that moderate CIMR alters LV strain after postero-lateral MI. Methods/Results Postero-lateral MI was created in 10 sheep. Cardiac MRI with tags … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Active and passive myocardial constitutive laws were previously described by Guccione et al [20,21] Prior to virtual MitraClip, the passive stiffness parameter, C, and contractility parameter, Tmax, for MI, borderzone and remote regions were inversely calculated by minimizing the difference between modeled and experimentally determined LV volume and regional strain [22] using established methods. [23] The optimized values for C and Tmax for MI, borderzone and remote regions were previously reported.…”
Section: Methodsmentioning
confidence: 99%
“…Active and passive myocardial constitutive laws were previously described by Guccione et al [20,21] Prior to virtual MitraClip, the passive stiffness parameter, C, and contractility parameter, Tmax, for MI, borderzone and remote regions were inversely calculated by minimizing the difference between modeled and experimentally determined LV volume and regional strain [22] using established methods. [23] The optimized values for C and Tmax for MI, borderzone and remote regions were previously reported.…”
Section: Methodsmentioning
confidence: 99%
“…[13,14] The LV myocardium was divided into MI, borderzone, and remote regions, where the borderzone-remote boundary was defined as the point where wall thickness is 70% of maximum LV wall thickness. The average area of the infarct zone as a percent of total LV area was 21%, with a range of 14–26%; the method for calculating this area has been previously described [32]. To model the mitral apparatus, the leaflets were constructed from B-spline curves approximating the leaflet contours, edge chords were attached to the free borders of each leaflet, and strut chords attached to the mid-section of each leaflet, as described by Wenk.…”
Section: Methodsmentioning
confidence: 99%
“…recently showed that moderate IMR increases strain in the radial-circumferential direction and may be a trigger for adverse remodeling in the infarct borderzone. [32] Despite a large body of evidence suggesting that strain stimulates adverse remodeling, the contributions of various strain components are not known. As such, the longitudinal strain increase identified in this study may not be the exclusive strain component leading to repair failure.…”
Section: Commentmentioning
confidence: 99%
“…First, in areas of healthy tissue bordering regions of infarct (the MI borderzone), high mechanical load and abnormal contractile protein function decrease the contractility of viable myocardium [26, 27]. Second, after prolonged ischemia, hibernating myocardium may be thinned and hypo- or akinetic, but undergo reverse remodeling and recovery of normal contractile function after revascularization [28].…”
Section: Commentmentioning
confidence: 99%